The Circumcision of Christ: Romans 15.7-13 - Garroway, Joshua D. (2012)
This article proposes that the term διάκονος περιτομη̑ς in Rom. 15.8 refers to Christ as an ‘agent of circumcision’, not a ‘servant to the circumcision’. As such, it is part and parcel of Paul’s view that faith in Christ effects in Gentile believers an intangible, genital circumcision, enabling them to enter the Abrahamic covenant which has circumcision as a requirement.
Keywords: Servant; Romans; Paul; Gentile; Circumcision